1995
DOI: 10.1002/jcb.240580108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular anatomy of an endodermal gland: Investigations on mucus glycoproteins and cell turnover in Brunner's glands of didelphis verginiana using lectins and PCNA immunoreactivity

Abstract: Brunner's glands are located in the submucosa of the proximal duodenum and are unique to mammalian species. The North American opossum (Didelphis virginiana) is generally regarded as a prototype marsupial that closely resembles fossil didelphids which can be placed at the beginning of mammalian evolution. The current investigation provided an opportunity for the analysis of secretory products from these glands in a species thought to be more closely related to earlier evolutionary forms. Extracts of Brunner's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
4
6
0
Order By: Relevance
“…However, in a few species the distribution and morphology of the Brunner's glands deviated from the general pattern. In the South American opossum, as has also been reported for Didelphis virginia (Schumacher and Krause, 1995), the Brunner's glands were confined to a very narrow region, immediately distal to the pyloric sphincter. In comparison with the other mammals examined, the secretory units of Brunner's glands in the raccoon were more dilated and lined with flatter cells.…”
Section: Discussionsupporting
confidence: 67%
“…However, in a few species the distribution and morphology of the Brunner's glands deviated from the general pattern. In the South American opossum, as has also been reported for Didelphis virginia (Schumacher and Krause, 1995), the Brunner's glands were confined to a very narrow region, immediately distal to the pyloric sphincter. In comparison with the other mammals examined, the secretory units of Brunner's glands in the raccoon were more dilated and lined with flatter cells.…”
Section: Discussionsupporting
confidence: 67%
“…The dot-blot system hence only detected PAS-and AB-positive glycoproteins. Furthermore, PAS staining of SDS gels showed that PAS-positive material in the perfusate had either a molecular mass of Ͼ600 kDa or Ͻ60 kDa, consistent with previous studies (35,37) in which PAS-stained PAGE of crude or gel-purified mucins revealed bands that barely penetrated the gel. Mucins are the only very high-molecular-mass (Ͼ600 kDa) glycoproteins that are likely to be present in an intestinal perfusate.…”
Section: Discussionsupporting
confidence: 73%
“…High and low molecular markers from Pharmacia (Piscataway, NJ) were used. Gels were stained with Coomassie brilliant blue R-250 (CBB; Bio-Rad) or PAS, as described previously (17,35,37).…”
Section: Perfusate Glycoprotein Concentration Measurementmentioning
confidence: 99%
“…In addition to reducing the gastric acidity when released in the duodenal lumen, EGF is thought to play an important role in accelerating the turnover of epithelial cells in the intestinal coating (Schumacher & Krause, 1995).…”
Section: Discussionmentioning
confidence: 99%